Trade liberalization and employment effects in Ukraine - Atanas Christev; Olga Kupets; Hartmut Lehmann (Institute for the Study of Labor (IZA), 2005)
This paper addresses the important issue of the effects of trade liberalization on labor market job flows. It studies the case of Ukraine where we view the sudden openness of the economy to trade as a quasi-natural experiment. We use disaggregated data on manufacturing industries and customs data on trade flows taking account of shifting trade patterns after the disintegration of CMEA trade regime. We provide some first evidence that three-digit NACE sector job flows are predominantly driven by idiosyncratic factors within industries. Other things equal, there is increased labor shedding as larger non-state share in industry relates to less job creation and more job destruction. Trade openness does affect job flows in Ukrainian manufacturing disproportionately according to trade orientation. We find that while trade with CIS decreases job destruction, trade with the EU increases excess reallocation mainly through job creation.
Keywords: E24; F14; J63; P23; 330; job creation; job destruction; trade flows and trade liberalization; Ukraine; Außenhandelsliberalisierung; Beschäftigungseffekt; Außenhandelsstruktur; Ukraine